A rare case of suprasellar arachnoid cyst with giant perimesencephalic and mesial temporal extension - physiopathological mechanisms - Dana Mihaela Turliuc; A. I. Cucu; B. Dobrovăț; Daniela Trandafir; Ş. Turliuc; Gabriela Florența Dumitrescu; Claudia Florida Costea (Romanian Neurosurgery, 2016)
The arachnoid cyst is a lesion commonly encountered in neurosurgery, especially in pediatric pathology. We are presenting the case of an adult patient with a suprasellar arachnoid cyst with giant perimesencephalic and mesial temporal extension discovered incidentally, where there is a discrepancy between the spectacular neuroimaging and the non-specific symptomatology. Some of the physiopathological mechanisms which led to the evolution of the cyst will also be presented.